Enhancing systemic resistance in faba bean (Vicia faba L.) to Bean yellow mosaic virus via soil application and foliar spray of nitrogen-fixing Rhizobium leguminosarum bv. viciae strain 33504-Alex1 - Abdelkhalek, Ahmed; El-Gendi, Hamada; Al-Askar, Abdulaziz A.; Maresca, Viviana; Moawad, Hassan; Elsharkawy, Mohsen M.; Younes, Hosny A.; Behiry, Said I. (Frontiers in Plant Science, 2022)
Rhizobium sp. manifests strong nitrogen fixation ability in legumes. However, their significance as biocontrol agents and antivirals has rarely been investigated. Under greenhouse conditions, the molecularly identified nitrogen-fixing plant growth-promoting rhizobacteria, Rhizobium leguminosarum bv. viciae strain 33504-Alex1, isolated from the root nodules of faba bean plants, was tested as a soil inoculum or a foliar application to trigger faba bean plants resistance against Bean yellow mosaic virus (BYMV) infection. Compared to the non-treated faba bean plants, the applications of 33504-Alex1 in either soil or foliar application significantly promoted growth and improved total chlorophyll content, resulting in a considerable reduction in disease incidence and severity as well as the accumulation level of BYMV in the treated faba bean plants. Furthermore, the protective activities of 33504-Alex1 were associated with significant reductions in nonenzymatic oxidative stress markers (H2O2 and MDA) as well as remarkably increased DPPH free radical scavenging activity and total phenolic content compared to the BYMV treatment at 20 days post-inoculation. Additionally, an increase in reactive oxygen species scavenging enzymes (SOD, CAT, and PPO) as well as induced transcriptional levels of pathogenesis-related proteins (PR-1, PR-3, and PR-5) were observed. Of the 19 polyphenolic compounds detected in faba bean leaves by HPLC analysis, gallic and vanillic acids were completely shut down in BYMV treatment. Interestingly, the 33504-Alex1 treatments were associated with the induction and accumulation of the most detected polyphenolic compounds. Gas chromatography-mass spectrometry (GC-MS) analysis showed hexadecanoic acid 2,3-dihydroxypropyl ester, tetraneurin-A-Diol, oleic acid, and isochiapin B are the major compounds in 33504-Alex1 culture filtrate ethyl acetate extract, suggesting it acts as an elicitor for the induction of systemic acquired resistance in faba bean plants. Consequently, the capacity of R. leguminosarum bv. viciae strain 33504-Alex1 to enhance plant growth and induce systemic resistance to BYMV infection will support the incorporation of 33504-Alex1 as a fertilizer and biocontrol agent as well as offer a new strategy for crop protection, sustainability, and environmental safety in agriculture production.